CUSTOMERS’ INTENTION ON PURCHASING AIRLINES E-TICKET: THE ANALYSIS OF ONLINE TRUST AND TECHNOLOGY ACCEPTANCE MODEL IN GARUDA INDONESIA WEBCOMMERCE - Sari, Devi Permata; Rofiq, Ainur (Jurnal Ilmiah Mahasiswa FEB, 2013)
CUSTOMERS’ INTENTION ON PURCHASING AIRLINES E-TICKET: THE ANALYSIS OF ONLINE TRUST AND TECHNOLOGY ACCEPTANCE MODEL IN GARUDA INDONESIA WEBCOMMERCE. This study purposes to examine and  analyse customer’s intention on purchasing airlines e- ticket with case in Garuda Indonesia’s e-ticket. In this study, the factors that effect customers’ purchase intention are online trust and Technology Acceptance Model, which consists of perceived usefulness (PU) and perceived ease- of- use (PEOU). The research was conducted at Faculty of Economic and Business University of Brawijaya by using survey methodology. The respondents or sample was choosen as 169 samples based on purposive sampling, which the respondents taken by some criterias. The data were analyzed by  using SPSS 19(IBM SPSS 19). The result of this research showed that customers’ purchase intention of e-ticketing is effected by perceived usefulness factor. It means that people are more concern with the value they get by buying online ticket than any other factors ( online trust and perceived ease- of- use). Key words: E- ticketing, online trust, Technology Acceptance Model, perceived usefulness, perceived ease- of- use, purchase intention, Garuda Indonesia.